2016
DOI: 10.4028/www.scientific.net/kem.697.691
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Carbon Nanotubes from Phenolic Resin Using Nickel Nitrate as a Catalyst Precursor

Abstract: Carbon nanotubes (CNTs) with 20-40 nm in diameter and several micro-meters in length were prepared through catalytic pyrolysis of phenol resin at 400-1000 °C under Ar atmosphere using nickel nitrate as a catalyst precursor. Microstructure and morphology of pyrolysed resin were characterised by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The results showed that the onset and optimal growth temperatures of CNTs were 400 and 800 °C respectively. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Considerable efforts have been made to prepare graphitic carbon by using Fe, Co or Ni as a catalyst and it has been found that these catalysts are effective in enhancing graphitization of amorphous carbon at a reduced temperature [3]. For example, in our previously published literatures, carbon nanotubes (CNTs) with 40-100 nm in diameter and tens of micrometers in length were respectively synthesized using ferric nitrate, nickel nitrate and cobalt nitrate as catalyst precursors at 600-1000 °C [7][8][9]. The results showed that these nitrate precursors firstly decomposed into corresponding metal oxides and then in-situ transformed to transition metal nanoparticles (Fe, Co and Ni) in a heat-treated process, the formed metal nanoparticles acted as a catalyst to catalyze the carbon containing gases released from the phenolic resin pyrolysis forming CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been made to prepare graphitic carbon by using Fe, Co or Ni as a catalyst and it has been found that these catalysts are effective in enhancing graphitization of amorphous carbon at a reduced temperature [3]. For example, in our previously published literatures, carbon nanotubes (CNTs) with 40-100 nm in diameter and tens of micrometers in length were respectively synthesized using ferric nitrate, nickel nitrate and cobalt nitrate as catalyst precursors at 600-1000 °C [7][8][9]. The results showed that these nitrate precursors firstly decomposed into corresponding metal oxides and then in-situ transformed to transition metal nanoparticles (Fe, Co and Ni) in a heat-treated process, the formed metal nanoparticles acted as a catalyst to catalyze the carbon containing gases released from the phenolic resin pyrolysis forming CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that the peak heights of graphite increased with increasing the Fe catalyst from 0 to 1.0 wt %, indicating the gradually enhanced graphitization degree of HGCS. However, they adversely decreased upon further increasing the Fe catalyst to 1.5–2.0 wt %, which might be caused by the aggregation and deactivation of the Fe nanoparticles due to their excessive amount [ 25 ]. Raman spectra of the samples ( Figure 4 ) further revealed that the maximal I G /I D ratio (0.99) was reached upon using 1.0 wt % Fe catalyst.…”
Section: Resultsmentioning
confidence: 99%